Using Communicative Language Teaching among English Teachers at A Senior High School in Riau - Idham Syahputra (Indonesian Journal of Integrated English Language Teaching, 2018)
The study aimed to identify the implementation of Communicative Language Teaching (CLT) in the teaching of English as a foreign language, specifically in speaking and listening, to find out the teachers’ understanding of CLT, and to identify any problems in the use of CLT in the teaching of English as a foreign language. The major findings showed that there was a broad use of most elements of CLT in the classrooms. Teachers were not yet able to conduct the production stage-communicative activities. They designed pair or group activities that reflect only parts of the practice stage in which activities are more controlled by the teachers than the learners. They recognized that their difficulties in adopting CLT is due to their unfamiliarity of the new concept of language teaching embedded in CLT and their limited proficiency in English. The main problem to using CLT was students’ reaction and attitudes, specifically during pair and small group work. Other problems included students’ lack of confidence in their speaking ability, embarrassment, and inability to express their opinion, ask questions, and be innovative during conversation practice.